2003
DOI: 10.1017/s0317167100002390
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Neurosurgical Trainees

Abstract: Background:Medical students in Canada must make career choices by their final year of medical school. Selection of students for a career in neurosurgery has traditionally been based on marks, reference letters and personal interviews. Studies have shown that marks alone are not accurate predictors of success in medical practice; personal skills and attributes which can best be assessed by letters of reference and interviews may be more important. This study was an attempt to assess the importance of, and abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…1 Furthermore, most neurosurgery residency programs are designed with an academic career in mind, which manifests predominantly as a mandatory one-to-two years of additional research compared to residencies of other subspecialties, and an encouragement by faculty for residents to engage in research, with relatively few programs preparing residents for the socioeconomic complexities of private practice neurosurgery. [3][4][5][6] Consequently, the relatively low numbers of resident graduates choosing academic neurosurgery has been somewhat surprising; a recent American Association of Neurological Surgeons census revealed that only 24% of graduates between 2000 and 2006 (613 neurosurgeons total) described their practice as academic. 1 This disparity between the number of graduates choosing private practice compared to academic neurosurgery has led to the search for factors that can potentially predict applicant and resident career choices.…”
Section: Discussionmentioning
confidence: 99%
“…1 Furthermore, most neurosurgery residency programs are designed with an academic career in mind, which manifests predominantly as a mandatory one-to-two years of additional research compared to residencies of other subspecialties, and an encouragement by faculty for residents to engage in research, with relatively few programs preparing residents for the socioeconomic complexities of private practice neurosurgery. [3][4][5][6] Consequently, the relatively low numbers of resident graduates choosing academic neurosurgery has been somewhat surprising; a recent American Association of Neurological Surgeons census revealed that only 24% of graduates between 2000 and 2006 (613 neurosurgeons total) described their practice as academic. 1 This disparity between the number of graduates choosing private practice compared to academic neurosurgery has led to the search for factors that can potentially predict applicant and resident career choices.…”
Section: Discussionmentioning
confidence: 99%
“…While a majority of medical schools in North America use personal essays, reference letters and interviews 13–15 to gain insight into non‐cognitive characteristics, there is little evidence regarding the effectiveness of these criteria. The limited data available regarding the relationship between non‐academic admissions criteria, medical school performance and residency ranking suggest that non‐academic criteria are important in predicting success beyond medical school 6,16–19 …”
Section: Introductionmentioning
confidence: 99%
“…The limited data available regarding the relationship between non-academic admissions criteria, medical school performance and residency ranking suggest that non-academic criteria are important in predicting success beyond medical school. 6,[16][17][18][19] In this study we attempted to assess the predictive validity of medical school application components in a novel fashion, by estimating the association between the components of the University of Toronto medical school application process and the ranking of students by 2 major postgraduate residency programmes at the University of Toronto. The rank given to a medical student by a residency programme was used as an outcome variable reflecting competencies in both cognitive and non-cognitive domains.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies that try to identify what makes a good resident. 1 , 2 Factors like academic inclination, clinical reviews, reference letters, personal statements, and interviews are all taken into account by the reviewing body and used to make a gestalt of each individual, which is then tested by the interview process. It is truly a subjective process that is imperfect and based on tenets that are unclear to both the candidate and the program.…”
mentioning
confidence: 99%
“…One of the most important abilities of a resident physician is the ability to cope with stress. 1 A prior study on attitudes of staff neurosurgeons towards incoming neurosurgery residents is that the ability to handle stress is a skill that is more difficult to teach and more important to have when entering. I did not know how I would handle failure beforehand, but now I know that I am able to tolerate and recover from failure related stress relatively effectively.…”
mentioning
confidence: 99%